2018
DOI: 10.11594/jtls.08.01.04
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Coenzymes on Mercury (Hg2+) Bioremediation by Isolates Pseudomonas aeruginosa KHY2 and Klebsiella pneumonia KHY3

Abstract: Mercury pollution is dangerous to health. Previous research was found two potential Gram-negative bacteria for mercury bioremediation, from gold mining in Central Kalimantan, Indonesia. These isolates were identified as Pseudomonas aeruginosa KHY2 and Klebsiella pneumonia KHY3. Mechanisms of mercury bioremediation had not known yet by these isolates. This study purposed to test the role of coenzymes on mercury bioremediation by these isolate and to determine the coenzymes best level of mercury bioremediation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(12 reference statements)
0
2
0
1
Order By: Relevance
“…Bacteria, such as Pseudomonas sp., Bacillus sp., Acinetobacter sp., Stenotrophomonas sp., Rhodococcus sp., and Burkholderia sp., have been isolated from actively stored soil and leachate in the literature (Imron et al 2019). It is also reported that P. aeruginosa isolated from leachate of solid waste landfills can remove about 29, 30, 35, and 28% of Pb, Cr, Ni, and Cd, respectively, and P. aeruginosa KHY2 and Klebsiella pneumonia KHY3 isolated from gold mine wastewater can reduce 1000 mg L -1 Hg by up to 60% (Neneng and Gunawan 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Bacteria, such as Pseudomonas sp., Bacillus sp., Acinetobacter sp., Stenotrophomonas sp., Rhodococcus sp., and Burkholderia sp., have been isolated from actively stored soil and leachate in the literature (Imron et al 2019). It is also reported that P. aeruginosa isolated from leachate of solid waste landfills can remove about 29, 30, 35, and 28% of Pb, Cr, Ni, and Cd, respectively, and P. aeruginosa KHY2 and Klebsiella pneumonia KHY3 isolated from gold mine wastewater can reduce 1000 mg L -1 Hg by up to 60% (Neneng and Gunawan 2018).…”
Section: Introductionmentioning
confidence: 97%
“…P. aeruginosa isolated from solid waste disposal dumpsite leachate can remove approximately 29, 30, 35, and 28% of Pb, Cr, Ni, and Cd, respectively [19]. Neneng and Gunawan [20] reported that P. aeruginosa KHY2 and Klebsiella pneumonia KHY3 isolated from gold mine wastewater exhibited the capability to remove 1000 mg L − 1 of Hg up to 60%. De et al [21] claimed that P. aeruginosa strain CH07 isolated from marine sediments could remove up to 95% of Hg at 8 mg L − 1 of Hg and 8 g L − 1 of NaCl.…”
Section: Introductionmentioning
confidence: 99%
“…Одни катионы являются для энзимов необходимыми коферментами[12][13][14], без которых невозможно протекание реакции. Другие, в том числе тяжелые металлы, загрязнение которыми вызывает определенные опасения, ингибируют эти процессы[15, 16].Было исследовано влияние хлоридов ионов Mg 2+ , Мn 2+ , Ва 2+ , Са 2+ на активность очищенного препарата. Показано, что магний в небольших концентрациях (до 3 мМ) активирует НАДФ + -зависимый МДГ (рис.2.).…”
unclassified